Biodiversity conservation and carbon storage of Acacia catechu willd. Dominated northern tropical dry deciduous forest ecosystems in north-western Himalaya: Implications of different forest management regimes - Kumar, Dhirender; Thakur, C. L.; Bhardwaj, D. R.; Sharma, Nidhi; Sharma, Prashant; Sankhyan, Neeraj (Frontiers in Environmental Science, 2022)
Sustainable forest management is the key to biodiversity conservation, flow of resources and climate change mitigation. We assessed the impact of various forest management regimes (FMRs): legal felling series [(reserve forest (RF), demarcated protected forest (DPF), un-demarcated protected forest (UPF), co-operative society forest (CSF) and un-classed forest (UF)] on biodiversity conservations and carbon storage in Acaciacatechu Willd. Dominated northern tropical dry deciduous forest ecosystems in Nurpur Forest Division of north-western Himalaya, India. The study revealed significant variations in floristic composition, biodiversity indices, population structure and C storage potential among different forest management regimes. The RF and DPF were found to be rich in species diversity and richness whereas the Simpson dominance index for trees and shrubs was maximum in UF and UPF, respectively. The diversity of understory herbs were higher in CSF and UF. The maximum density of seedlings, saplings and poles were recorded in RF followed by DPF and UPF, whereas the minimum density was found in CSF. The tree C density (69.15 Mg C ha−1) was maximum in UF closely followed by RF; whereas the minimum was recorded in CSF (33.27 Mg C ha−1). The soil C density was maximum in RF (115.49 Mg C ha−1) and minimum in CSF (90.28 Mg C ha−1). Similarly, the maximum total ecosystem C density was recorded in RF (183.52 Mg C ha−1) followed by DPF (166.61 Mg C ha−1) and minimum in CSF (126.05 Mg C ha−1). Overall, UF management regimes were shown to have a greater capacity for C storage in vegetation, whereas strict FMRs, such as RF and DPF, were found to be more diverse and have a higher soil and ecosystem carbon density. The study established that in the midst of climate and biodiversity emergencies, it is urgent to maintain, protect and strengthen the network of RF and DPF FMRs for biodiversity conservation, climate change adaptation and mitigation.